Advancing Primed Goal Research in Organizational Behavior. Issue 1 (25th September 2020) - Chen, Xiao; Latham, Gary P.; Piccolo, Ronald F.; Itzchakov, Guy
Abstract : In this rejoinder, we address three issues discussed in the commentaries on our lead article: possible ethical issues in goal priming in organizational settings, whether goal priming is restricted to routine behaviors, and the relationship of goal priming with self‐fulling prophecies and an organization's climate. Finally, our data were examined by an independent researcher who tested for publication bias.